Post-transcriptional regulation in early cell fate commitment of germ layers - Rubens Gomes-Júnior; Cintia Delai da Silva Horinouchi; Aruana Fagundes Fiuza Hansel-Fröse; Annanda Lyra Ribeiro; Isabela Tiemy Pereira; Lucia Spangenberg; Bruno Dallagiovanna (BMC Genomics)
Abstract Background Cell differentiation during development is orchestrated by precisely coordinated gene expression programs. While some regulatory mechanisms are well understood, there is a significant room to explore unresolved aspects of lineage choice and cell-fate decisions, as many events in these processes are still not fully elucidated. Given that, gene expression is influenced not only by transcriptional control but also by post-transcriptional events. Here, we described the presence of post-transcriptional regulation on gene expression during lineage commitment across all three embryonic germ layers. We employed monolayer differentiation protocols to map early transcriptional and post-transcriptional events in human embryonic stem cell specification. This approach included obtaining representative populations from the three germ layers, followed by sequencing of both polysome-bound and total RNAs. Results We characterized our model by its unique expression profile and the presence of specific markers for each differentiation. RNA sequencing revealed a consistent pattern of gene upregulated and downregulated when comparing the transcriptome and translatome during the differentiation of all three germ layers. By comparing these datasets, we identified genes subjected to post-transcriptional regulation in all germ layer differentiations and categorized the nature of this regulation. GO analysis demonstrated that polysome profiling serves as a complementary technique, capturing nuances that may be overlooked when analyzing only the transcriptome. Finally, we directly compared the transcriptome and translatome to identify genes actively recruited to the translation machinery, uncovering unique features specific to each germ layer. Conclusions Substantial post-transcriptional modulation was found during germ layer commitment, emphasizing the translatome potency in capturing nuanced gene expression regulation. These findings highlight the post-transcriptional regulation’s critical role in early embryonic development, offering new insights into the molecular mechanisms of cell differentiation.